Prevalence, Isolation of Bacteria and Risk Factors of Mastitis of Dairy Cattle in Selected Zones of Oromia Regional States, Ethiopia (Global Journal of Medical Research, 2016)
A cross sectional study was conducted on a total of 471 cross and pure borana breed dairy cattle to determine prevalence of clinical and subclinical mastitis using CMT in selected districts of North Showa and Borana zones of pastoral area from April 2012 to February 2014. The overall mastitis prevalence was 237(50.3%). The cow level prevalence was 9.5% clinical and 40.7% were subclinical cases. Of 1884 quarters examined 10(0.5%) quarters were blind teats and quarters 550(50.2%) were showed mastitis. High score CMT positive milk sample were investigated using standard microbiological techniques. Identification of bacterial isolates revealed that 10 types of bacterial isolates were identified. The isolated bacteria were Staphylococcus aureus and CNS 20 (37.7%), Diplococcus spp 2 (3.8%), Corynebacterium pseudotuberclosis 3(5.8%), Corynebacterium bovis 1(1.7%), Micrococcus spp 1(1.9%), Pseudomonas spp 1(1.9%), Bacillus spp 1(1.9%), E. coli 3(5.7%) Proteus spp 1(1.9%). Different risk factors like parity number, farming hygiene, animal origin and husbandry type were considered. Hygienic conditions and husbandry type were the most important potential risk for mastitis.
Keywords: CMT; bacterial culture; mastitis; prevalence; bovine; borana; north showa